2013
DOI: 10.1360/032013-9
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific bioaccumulation of polybrominated diphenyl ethers, hexabromocyclododecan and dechlorane plus in biota: A review

Abstract: Polybrominated diphenyl ethers (PBDEs), hexabromocyclododecans (HBCDs) and dechlorane plus (DPs) are ubiquitous contaminants that are found in numerous matrices around world. They have been proven to be environmentally persistent, bioaccumulative, and toxic to biota, and subject to long-range transport. Technical PBDE mixtures consist of congeners with different bromine content. HBCDs were consisting of three diasteroisomers (-, and -HBCD) and these three isomers are chiral and occur as racemates in technic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…This could be a reason for low f anti values found in waterbirds. On the contrary, no study has reported a clear isomer-selective bioaccumulation of syn-DP in terrestrial birds (Luo et al, 2013). Since few studies simultaneously reported the isomer composition of DP in terrestrial birds and their diet sources, it is hard to drawn a conclusion on isomer-selective bioaccumulation of DP in terrestrial birds.…”
Section: Isomer-specific Bioaccumulation Of Dp In Different Tissuesmentioning
confidence: 97%
“…This could be a reason for low f anti values found in waterbirds. On the contrary, no study has reported a clear isomer-selective bioaccumulation of syn-DP in terrestrial birds (Luo et al, 2013). Since few studies simultaneously reported the isomer composition of DP in terrestrial birds and their diet sources, it is hard to drawn a conclusion on isomer-selective bioaccumulation of DP in terrestrial birds.…”
Section: Isomer-specific Bioaccumulation Of Dp In Different Tissuesmentioning
confidence: 97%
“…These studies provide further concerns on the potential threat of DP to human health and ecosystems. A few reviews (Feo et al, 2012;Luo et al, 2013;Sverko et al, 2011a;Vorkamp and Rigét, 2014;Xian et al, 2011) have presented the properties, analytical methods and environmental levels of DP and related compounds in the past several years. This review is aimed at summarizing our current understanding of DP in the environment, including analytical methods, emission sources, and the environmental behaviors.…”
Section: Introductionmentioning
confidence: 99%